DESCRIPTION OF DRINKING WATER IN COMPLIANCE WITH HYGIENIC STANDARDS (Лучшие интеллектуальные исследования, 2025)
Abstract. Violation of the quality and natural condition of the waters can damage human health due to the fact that the water contains a large amount of infectious diseases-mosquito microorganisms, or due to an increase in worm eggs or an increase in the content of various chemicals in the water, but rather a decrease in it. The provision of centralized water supply to settlements reduces the incidence rate while improving the sanitary lifestyle of the population.